Price discovery in cattle and measuring market thinness - Brookover, Elena Katherine (Kansas State University, 2020)
Economists and market participants have long been concerned that declining participation in negotiated cash sales of live cattle could have adverse impacts on the cash market and beyond. Economic incentives have led to a shift toward formula trading and this shift has left a relatively small group to carry the load of total cash negotiations. It is presumed that negotiated cash prices are used as base prices in formula sales meaning that the 65% of cattle sold via formula are priced based on 21% of live cattle sold as negotiated transactions (USDA Livestock, Poultry, & Grain Market News, 2019). The goal of this paper is to determine how thin the negotiated cash market for live and dressed cattle, as well as the beef cutout, can become and still represent an accurate market price. Following previous work in market hogs and live cattle markets, I applied Chebyshev’s inequality to weekly negotiated live and dressed cattle sales in the five major price-reporting regions and the beef cutout to determine the number of transactions needed to arrive at a price that meets an acceptable accuracy criterion. I extended the method to consider average annual transaction levels, as others have done, but also weekly levels. In both cases, I show at what points in time regions have or have not had sufficient negotiated trade to maintain pricing accuracy. Results show that outside of certain market shocks in 2003 and between 2014 and 2017 there continues to be sufficient trade in the negotiated cash market.
Keywords: Cattle; Price Discovery; Market Thinness; Chebyshev's Inequality